INVESTIGATING THE RELATIONSHIP BETWEEN CITY DISTRICTS AND SPORTS CLUBS FREQUENCY IN SHIRAZ CITY - Mahdieh Ardaneh; Hanieh Rasekh; Ehsan Amiri-Ardekani (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2021)
Assessing the capacity and quality of sports equipment is important to develop a better understanding of sport participation.Different organizations are involved in the preparation of sports-related services. So, policymakers need to design a framework to give people access to sports facilities. We hypothesized geographical access to sports facilities can affect sports participation in Shiraz. The list of sports clubs was matched with Shiraz districts in 2020. The significance of the relationship between area, the population of each region, per capita construction budget, frequency of clubs, green area, number of parks, population to number of club's ratio, and area to the number of club's ratio indicators and the number of sports clubs were analysed by SPSS version.22. There were statistically significant relationships between district and population of each region, District and sports club, District and Population to the number of clubs, area andgreen area, per capita construction budget and the number of parks, per capita construction budget, and population of each region (p<0.05).Significant correlation between the districts and the Population to the number of clubs ratio shows that there is no proper distribution of sports facilities in different urban areas. So, people may not have adequate access to sports facilities. Also, the correlation was observed between total area and green area, per capita construction budget, and the number of parksand Per capita construction budget and the population of each region that shows the health level of the people who live in undeveloped districts is endangered and needs more attention.